2013
DOI: 10.1179/1743288x13y.0000000103
|View full text |Cite
|
Sign up to set email alerts
|

Innovations in interprofessional learning and teaching: providing opportunities to embed patient safety within the pre-registration physiotherapy curriculum. A Pilot Study

Abstract: Background: Despite recognition of the need to embed patient safety within undergraduate healthcare education, there are limited examples of how this has been achieved within physiotherapy. The purpose of this regional initiative was to develop a course and teaching resources to support Higher Education Institutions in the United Kingdom (UK) when embedding the World Health Organization (WHO) multiprofessional patient safety curriculum into undergraduate healthcare education. Objectives: In this pilot study, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…Senette, O’Malley, and Hendrix () reported improved interaction with students from other disciplines, while also highlighting an increased awareness of the importance of two way communication. Gough et al (), Buckley et al (), and Lachmann et al () also found benefits of improved communication skills, although this could be due to extensive presimulation learning materials, rather than the simulation alone (Buckley et al, ; Gough et al, ), or the prolonged nature of the learning experience (Lachmann et al, ). However, two studies (Bolesta & Chmil, ; Ohtake et al, ) found no significant improvement in communicating with other healthcare professions.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Senette, O’Malley, and Hendrix () reported improved interaction with students from other disciplines, while also highlighting an increased awareness of the importance of two way communication. Gough et al (), Buckley et al (), and Lachmann et al () also found benefits of improved communication skills, although this could be due to extensive presimulation learning materials, rather than the simulation alone (Buckley et al, ; Gough et al, ), or the prolonged nature of the learning experience (Lachmann et al, ). However, two studies (Bolesta & Chmil, ; Ohtake et al, ) found no significant improvement in communicating with other healthcare professions.…”
Section: Introductionmentioning
confidence: 98%
“…A review of the literature shows an increase in simulation‐enhanced interprofessional education since the turn of the century, but many activities have involved only two professional groups; for example, only medical and nursing students (Bolesta & Chmil, ; Ohtake, Lazarus, Schillo, & Rosen, ; Reese, Jeffries, & Engum, ). When more professions have been involved, the simulated activity has either been single‐case simulations (Buckley et al, ; Titzer, Swenty, & Hoehn, ), which limits experiences; extended periods of time on a training ward (Hallin & Kiessling, ; Lachmann, Ponzer, Johansson, Karlgren, & Fossum, ; Ponzer et al, ), which are a challenge with larger student groups; or part of a wider learning activity (Gough, Jones, & Hellaby, ). Despite the variety of activities, the majority of studies indicate a positive impact on student confidence in skill performance (Ohtake et al, ), self‐confidence (Reese et al, ), and understanding the role of different professions in the patient journey (Buckley et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, studies that used interprofessional education activities involved interactive seminars, workshops or team-based simulation [20][21][22][23]. Often these educational interventions employed TeamSTEPPS or CRM (crisis resource management) approaches [24][25][26][27]. Studies reporting the use of interprofessional practice interventions tended to employ team checklists [28][29], team briefings [30,31] or patient safety rounds [32,33].…”
Section: Insert Table 2 About Herementioning
confidence: 99%
“…IPEC further notes that these competencies are an important part of forming a professional identity; however, overlapping interprofessional competencies can be a source of tension between professions (IPEC, 2011). Implementation of IPE has been supported by current and emerging research studies in chiropractic services, speech pathology, education, nursing, and medicine (Bajnok, Puddester, MacDonald, Archibald, & Kuhl, 2012;Bednarz & Lisi, 2014;Gough, Jones, & Hellaby, 2013;Morris & Matthews, 2014;Priest, Roberts, Dent, Blincoe, & Lawton, 2008;Suleman et al, 2014;Ying, Chiang, Chua, & Klainin-Yobas, 2012) as well as governmental and professional organizations (American Association of Colleges of Nursing [AACN], 2006[AACN], , 2008[AACN], , 2011Clarke & Hassmiller, 2013;Lutfiyya, Brandt, Delaney, Pechacek, & Cerra, 2016). Improving patient outcomes may be seen to be reliant on interdisciplinary cooperation and collaboration (Keene, Byington, & Samples, 2009;Nelson, King, & Brodine, 2008;Sterchi, 2007).…”
Section: Introductionmentioning
confidence: 99%